Correction: Research on distribution network fault processing technology based on knowledge of graph. - Qiang Li; Feng Zhao; Li Zhuang; Jiangwen Su; Xiaodong Zhang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0295421.].